The Effects of Breast Cancer Educational Intervention on Knowledge of Female Students in Grade XI Highschool - Hasyim, Husdayana Nur; Wulandari, Sri; Sukismanto, Sukismanto (Journal of Health Education, 2019)
Background: Breast Self-Examination (BSE) is very important for women and it would be better if they already have knowledge about BSE since adolescence and perform BSE since early period of time. Lack of appropriate and adequate information, especially about breast self-examination, makes female adolescents unable to detect breast cancer early. In fact, breast cancer is one that causes death in women. The efforts to increase knowledge of adolescents is health education. This study aim to identify the effect of health education about BSE on knowledge in eleventh grade students of SMA 1 Imogiri Bantul Yogyakarta.Methods: This research employed a pre-experimental design with a one-group pretest-posttest design. The population was 110 students in eleventh grade. Samples were taken using proportional random sampling with a sample size of 52 female students. Data were collected using a questionnaire and analyzed using Wilcoxon Test.Results: Students had adequate knowledge (71.2%) before being given health education and had good knowledge (100%) after being given health education. There was a significant effect of health education on knowledge in students with a p-value of 0.000 (p = 0.000 <0.05).Conclusion: There is a significant effect of health education about BSE on knowledge in students of SMA 1 Imogiri Bantul Yogyakarta.